2014
DOI: 10.4161/adip.29993
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2signals white-to-brown adipogenic differentiation

Abstract: Abbreviations: 15d-PGJ 2 , 15-deoxy-D 12,14 -prostaglandin J 2 ; 20-HETE, 20-hydroxy eicosatetraenoic acid; Akt, protein kinase B; ATP, adenosine triphosphate; ATGL, adipose triglyceride lipase; BAT, brown adipose tissue; BMPs, bone morphogenic proteins; cAMP, cyclic adenosine 3 0 , 5 0 -monophosphate; C/EBP, CCAAT enhancer binding protein; CIDEA, cell death-inducing DFFA-like effector a; COX, cyclooxygenase; FLAP, 5-lipoxygenase activating protein; IL, interleukin; LOX, lipoxygenase; LT, leukotriene; MCP-1, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…PLA2G10 activity leads to the release of PAF, prostaglandin E2 (PGE2), and 15-deoxy-delta12,14-prostaglandin J2 (PGJ2) by the hydrolysis of membrane phospholipids (50)(51)(52). Prostaglandins are thought to induce BeAT development (53); however, AKG treatment failed to induce PGE2 or PGJ2 release from ATMs (Supplemental Figure 13B). These findings suggest that AKGs act specifically through PAF.…”
Section: Resultsmentioning
confidence: 99%
“…PLA2G10 activity leads to the release of PAF, prostaglandin E2 (PGE2), and 15-deoxy-delta12,14-prostaglandin J2 (PGJ2) by the hydrolysis of membrane phospholipids (50)(51)(52). Prostaglandins are thought to induce BeAT development (53); however, AKG treatment failed to induce PGE2 or PGJ2 release from ATMs (Supplemental Figure 13B). These findings suggest that AKGs act specifically through PAF.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, both the expression of PPARγ and of TLR9 are dependent on the terminal adipogenic transcription factor C/EBPα. This possible interrelation on the level of transcriptional regulation might be responsible for increased TLR9 expression during late adipocyte differentiation (Takeshita et al 2004, Cristancho & Lazar 2011, Garcia-Alonso & Claria 2014.…”
Section: Discussionmentioning
confidence: 99%
“…[135][136][137][138][139] More importantly, recent studies suggest that another type of brown adipocytes, called beige or bright adipocytes, with similar functions to those of brown adipocytes could be recruited in WAT upon environmental stimulation and/or pharmacologic treatment (Figure 2). 134,140 Among these, García-Alonso et al 141,142 reported prostaglandin E2 as a key regulator of white-to-brown adipogenesis, while Schulz et al 143 showed that Sca-1 + adipogenic progenitor cells from murine subcutaneous white fat were highly inducible to differentiate into brown-like adipocytes upon stimulation with BMP7. In addition, Rosenwald et al 144 demonstrated that cold-induced bright or beige adipocytes in mice were reversed into white adipocytes on warm adaptation and that those white adipocytes converted into bright adipocytes on additional cold stimulation.…”
Section: Complexity Of Msc Adipogenesis As a Potential Therapeutic Tamentioning
confidence: 99%